Mechanically robust nacre-mimetic framework constructed polypyrrole-doped graphene/nanofiber nanocomposites with improved thermal electrical properties. (5th October 2018) - Wang, Zhong; Mo, Liuting; Zhao, Shujun; Li, Jianzhang; Zhang, Shifeng; Huang, Anmin
Abstract: Nacre mimetics show great potential as mechanically robust, lightweight, and promising functional materials. Herein, we report a nanostructured nacre-mimetic hybrid framework, prepared via in situ self-polymerization of tannic acid (TA) and pyrrole monomer on cellulose nanofiber (CNF)-anchored graphene nanosheets (GNs), as a two-dimensional interconnected network (designated as TA@PG-CNF) to fabricate mechanically robust and thermally and electrically conductive composites. A unique network structure with a combination of conductive polypyrrole (PPy) protrusions and multiscale nanofibers/nanoplates was obtained, where the nanohybrid protrusions acted as bridges that link the adjacent GNs and nanofibers. As a result, a composite with low filler loading (10.0 wt%) exhibited advantages for the combination of all properties, i.e., enhanced electrical and thermal conductivity (6.52 S cm −1 and 7.81 W m −1  K −1 ), high tensile strength (217.9 MPa), and good toughness (19.6 MJ m −3 ). We attribute the enhancement of these properties to the construction of an interconnected TA@PG-CNF skeleton and the oriented "brick-and-mortar" structure based on GNs blocks and the polyvinyl alcohol matrix, in which a mechanically robust conductive network was constructed. We envision that the relevant functionalities can be integrated into stiff and strong bioinspired materials as flexible microelectronic candidates. Graphical abstract: Unlabelled Image Highlights: We report on nacre-mimetic structure of graphene nanosheets/cellulose nanofiber film by generating polypyrrole nanohybrids. Natural tannic acid-induced the formation of the interconnected network acted as high efficient conductive networks. Significantly increased thermal and electrical conductivity were achieved at comparatively low filler content. Highly aligned network dominated the loading and heat transfer for strong and conductive graphene-based composites.